If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + -24 = 0 Reorder the terms: -24 + 3u = 0 Solving -24 + 3u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 3u = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 3u = 0 + 24 3u = 0 + 24 Combine like terms: 0 + 24 = 24 3u = 24 Divide each side by '3'. u = 8 Simplifying u = 8
| -6(-5x+2)=198 | | 0.89(4p+5)=4(0.5p-2) | | 8n-5=11-14 | | -4=-2h+6 | | 20v^2d-23vd+6d^2= | | 4y+12=-16 | | 10xm-3x(2xm-9)=9x(m-1)+1 | | 7(x-83)-3=2(x-8)+17 | | ln(x-2)+ln(x-3)=ln(x+1) | | 5x+8-7(x+1)=7x+5 | | 3x^3-2x^2=12x-8 | | 8=0.5(-m-1) | | p-(-58)=38 | | 144=x^2+7x | | y+.5y+2=4 | | 5x=17x+14 | | 32+4x=8x-56 | | 4k+9-6k=24 | | -3-2x+x=3 | | 4s^2=25s+21 | | 7x+15=25 | | (r+21)(r-24)=0 | | 0.3f+9.4+0.8=-3.8 | | m+7=-26 | | 5a-7=57 | | 8x-4+4x-2=6 | | 15s+-12+-10s=5 | | 6t+12= | | x^2+x+m+1=0 | | x-51=-30 | | -5(5x-2)=60 | | 3(c+5)=60 |